Design and assessment of tractor-driven chopping tilling and mixing machine for in-situ management of paddy straw - Abhishek Patel; Krishna Pratap Singh; Ajay Kumar Roul; Rohit Dilip Nalawade; Aman Mahore; Mohit Kumar; Shital Sonawane; Berhanu Kebede (Scientific Reports, 2024)
Abstract In many Indian regions, paddy wheat is the main crop rotation and facing the problem of straw incorporation for seed bed preparation in short period. The handling of straw in combine harvested paddy fields is a significant issue in the paddy wheat rotation. In order to solve this issue, efforts were carried out to cut paddy straw into small pieces by the newly proposed counter-rotating blades, followed by the simultaneous incorporation of a rotary tiller into the soil. Therefore, a tractor operated chopping cum tilling mixing machine was developed. In the study, three different blades (straw management system (SMS) Serrated, cutter bar and SMS plain) were tested in the terms of torque and required to chop the straw. SMS serrated blade was best suitable for the chopping mechanism as it required minimum cutting torque for the straw bunches. The developed chopping cum tilling mixing machine was tested at three different levels of forward speed (1.77, 2.3, and 3 km h−1), moisture content at three levels (35 ± 3.4, 24 ± 2.2 and 17 ± 2.6%) with fix rotary tiller rotational speed of 810 rev min−1. Optimum operating condition of the machine was obtained at a forward speed of 1.9 km h−1 and a moisture of 24%. At these optimized values, the mixing index (96%), mean weight diameter (7.9 mm), bulk density (1230 g cc−1) and fuel consumption (3 l h−1) were 96%, 7.9 mm, 1230 g cc−1 and 3.0 l h−1 respectively. The developed machine performs three operations i.e., chopping, tilling, and mixing in single pass for effective in-situ straw management.